Women and writing in medieval Europe : a sourcebook - Larrington, Carolyne (Routledge, 1995)
Carolyne Larrington has gathered together a uniquely comprehensive collection of writing by, for and about medieval women, spanning one thousand years and Europe from Iceland to Byzantiu. The extracts are arranged thematically, dealing with the central areas of medieval women's lives and their relation to social and cultural institutions. Each section is contextualised with a brief historical introduction, and the materials span literary, historical, theological and other narrative and imaginative writing. The writings here uncover and confound the stereotype of the medieval woman as lady or v.